2010
DOI: 10.1007/s10096-010-1034-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the in vitro antifungal drug susceptibility with the in vivo activity of fluconazole in a murine model of cerebral infection caused by Cryptococcus gattii

Abstract: Forty Cryptococcus gattii strains were submitted to antifungal susceptibility testing with fluconazole, itraconazole, amphotericin B and terbinafine. The minimum inhibitory concentration (MIC) ranges were 0.5-64.0 for fluconazole, <0.015-0.25 for itraconazole, 0.015-0.5 for amphotericin B and 0.062-2.0 for terbinafine. A bioassay for the quantitation of fluconazole in murine brain tissue was developed. Swiss mice received daily injections of the antifungal, and their brains were withdrawn at different times ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The in vitro MIC values were correlated with the in vivo response to the treatment with fluconazole or amphotericin B in that study. This correlation was also demonstrated previously (19) amphotericin B was also indifferent (17). Based on the Etest, Kontoyiannis et al (15) found an antagonistic interaction between itraconazole and amphotericin B against isolates of Aspergillus fumigatus.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The in vitro MIC values were correlated with the in vivo response to the treatment with fluconazole or amphotericin B in that study. This correlation was also demonstrated previously (19) amphotericin B was also indifferent (17). Based on the Etest, Kontoyiannis et al (15) found an antagonistic interaction between itraconazole and amphotericin B against isolates of Aspergillus fumigatus.…”
Section: Discussionsupporting
confidence: 72%
“…The plates were incubated at 35°C for 72 h (6). The MIC for fluconazole was determined visually as 80% growth inhibition, while for amphotericin B the reading was performed as 100% growth inhibition compared to the control (19). We also performed the MIC determination for fluconazole at 50% (the MIC-2 endpoint) of growth inhibition according to the CLSI method (6).…”
Section: Methodsmentioning
confidence: 99%
“…32 Recent epidemiological studies demonstrate that some strains of C. gattii , especially those of the VGII molecular type, have relatively low susceptibilities to fluconazole, with sustained susceptibility to voriconazole and posaconazole. 7174 Although no reported data correlates low susceptibility to fluconazole by minimal inhibitory concentration to clinical outcomes, our experience is that these other azoles might have relatively improved activity when used during the continuation phase of therapy, during which the goal is to maintain oral azole therapy for weeks to months (average 6 months) after the patient completed the induction phase of treatment with amphotericin B-based formulations. Therefore, further research is needed to prospectively evaluate treatment outcomes of C. gattii infections and minimal inhibitory concentration values with fluconazole.…”
Section: Antifungal Therapymentioning
confidence: 94%
“…This may be due to pCramoll not crossing the blood-brain barrier (Patricio et al, 2011) and not directly acting on the CNS. Meanwhile, fluconazole was present at higher concentration in the CNS after 14 days of use, reducing CFU in the brain (Mendes et al, 2010). Furthermore, pCramoll also stimulates C. gattii phagocytosis, increasing the early combat of the pathogen in the lungs.…”
Section: Discussionmentioning
confidence: 99%